The molecular mechanisms of plasticity in crystal forms of theophylline - Liu, Hongji (2023)
Plastic and elastic behaviors of organic crystals have profound influence on the processability of pharmaceutical substances. Analogous to metals, the identifications of molecular slip planes in organic crystals are regarded as a strategy for harnessing plasticity. In this work, we experimentally characterized the form II anhydrous theophylline (THPa) and its monohydrate (THPm) for their distinct plastic and elastic behaviors. Extensive DFT calculations were performed to model the effects of increasing lattice strains on molecular packing. We discovered that the energy barrier associated with the strain-induced molecular rearrangement would link to the plasticity of THPa, and possibly other simple aromatic compounds. Meanwhile, water molecules in THPm disrupt the stacking architecture from THPm and effectively undermine the general mechanism for plasticity. Hydrate formation would therefore be an alternative strategy to engineer the mechanical property of organic crystalline materials.